2020
DOI: 10.1039/c9tc07063j
|View full text |Cite
|
Sign up to set email alerts
|

Band gap of reduced graphene oxide tuned by controlling functional groups

Abstract: Functionalization of reduced graphene oxide with epoxide groups allows tuning its band gap energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(69 citation statements)
references
References 65 publications
(69 reference statements)
4
61
0
Order By: Relevance
“…This is consistent with experimental data that showed that the band gap of rGO can be tuned from 0.264-0.786 eV by controlling the surface concentration of epoxide groups. 67 The bulk a-MnO 2 was modelled tetragonal crystal structure (space group -I4/m, no. 87) in the antiferromagnetic AFM-C2 conguration 68 as shown in Fig.…”
Section: Density Functional Theory Analysesmentioning
confidence: 99%
“…This is consistent with experimental data that showed that the band gap of rGO can be tuned from 0.264-0.786 eV by controlling the surface concentration of epoxide groups. 67 The bulk a-MnO 2 was modelled tetragonal crystal structure (space group -I4/m, no. 87) in the antiferromagnetic AFM-C2 conguration 68 as shown in Fig.…”
Section: Density Functional Theory Analysesmentioning
confidence: 99%
“…Some folds and wrinkles were also identified on edge of the surface. These corrugations on the AArGO25 surface can modify its electronic structure, mechanical, optical, and chemical properties [ 22 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The peak intensity of the AArGO25 carbonyl group (C=O) was found to be higher than that of GO, attributing to a higher number of carbonyl elements of the AArGO25 material. These carbonyl OFGs form the defective surface of AArGO25 [ 22 ]. These defects are the main active sites for the adsorption of the CO 2 gas molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C1s of GO plotted in bottom half of figure shows peaks centered at ~285.1 and 287.14 eV corresponding to carbonyl (C-O) and carboxyl (C=O) moieties of graphene oxide whereas the minor peak at 288.8 eV is attributed to carboxylic (O=C-O) groups [ 54 ]. However, in MnO 2 @CNT-rGO a broad peak centered at 284.5 eV corresponding to sp 2 carbon (C=C) is dominating with minor peaks at 286.4, 288.8 and 291.5 eV attributed to residual epoxides [ 55 ], carboxylic and plasmon resonance of valence electrons of rGO [ 56 ]. In order to study the ionic states of manganese moieties in Mn-H 3 BTC MOF and MnO 2 @CNT-rGO, high-resolution XPS spectroscopy was carried out and the deconvoluted Mn 2p of the two samples is plotted n Figure 2 c. In case of Mn-H 3 BTC MOF, two distinct peaks at 641.96 and 650.8 eV corresponding to Mn 2p 3/2 and Mn 2p 1/2 with a peak distance of 8.84 eV is observed whereas in MnO 2 @CNT-rGO the peaks are centered at 641.66 and 653.4 eV with a substantially higher peak distance of 11.74 eV.…”
Section: Resultsmentioning
confidence: 99%